Subclinical Mastitis in Small-Holder Dairy Herds of Gansu Province, Northwest China: Prevalence, Bacterial Pathogens, Antimicrobial Susceptibility, and Risk Factor Analysis - Ling Wang; Shahbaz Ul Haq; Muhammad Shoaib; Jiongjie He; Wenzhu Guo; Xiaojuan Wei; Xiaohong Zheng (Microorganisms)
This cross-sectional study assessed the prevalence, bacterial distribution, antimicrobial susceptibility, and potential risk factors associated with subclinical mastitis (SCM) in small-holder dairy herds in Gansu Province, Northwest China. Forty small-holder cow farms were randomly selected from eight cities/counties in six districts of Gansu Province, and a total of n = 530 lactating cows were included in this study. SCM prevalence was noted at 38.87% and 9.72% at the cow and quarter levels, respectively, based on the California Mastitis Test (CMT). The prevalence of the recovered bacterial species was noted as follows: S. agalactiae (36.02%), S. aureus (19.43%), coagulase-negative staphylococci (CNS) (16.11%), S. dysgalactiae (12.80%), E. coli (9.00%), and S. uberis (6.64%). All isolated bacteria were 100% multi-drug-resistant (MDR) except S. aureus (87.8% MDR). Antimicrobial susceptibility profiles revealed the increased resistance (>85%) of these pathogens to penicillin, streptomycin, trimethoprim–sulfamethoxazole, vancomycin, and erythromycin. However, these pathogens showed increased susceptibility to ampicillin, amoxicillin–sulbactam, ceftazidime, neomycin, kanamycin, spectinomycin, norfloxacin, ciprofloxacin, and doxycycline. The multivariate regression analysis demonstrated that old age, high parity, late lactation, lesions on teats, previous history of clinical mastitis, higher milk yield, and milking training were found to be potential risk factors (p < 0.001) associated with developing SCM in small-holder dairy cows in Gansu Province, China. These findings highlight the need for routine surveillance, antimicrobial stewardship, and effective preventive strategies to mitigate SCM in small-holder dairy production and their possible impacts, i.e., increased antimicrobial resistance and infection, on public health.